2018
DOI: 10.2196/10319
|View full text |Cite
|
Sign up to set email alerts
|

A Remote Patient Monitoring Intervention for Patients With Chronic Obstructive Pulmonary Disease and Chronic Heart Failure: Pre-Post Economic Analysis of the Smart Program

Abstract: BackgroundExacerbation of chronic obstructive pulmonary disease (COPD) and chronic heart failure (CHF) are associated with high health care costs owing to increased emergency room (ER) visits and hospitalizations. Remote patient monitoring (RPM) interventions aim to improve the monitoring of symptoms to detect early deterioration and provide self-management strategies. As a result, RPM aims to reduce health resource utilization. To date, studies have inconsistently reported the benefits of RPM in chronic illne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…However, Vestergaard et al [ 12 ] found that the Danish TeleCare North HF trial led to cost savings and was cost-effective in terms of health-related quality of life in favour of the intervention. Isaran et al [ 13 ] studied remote patient monitoring in HF and chronic obstructive pulmonary disease (COPD), and found that the cost of emergency room visits and hospitalizations were reduced. For Germany, the CardioBBEAT trial investigated the cost-effectiveness of noninvasive telemonitoring as a primary endpoint.…”
Section: Introductionmentioning
confidence: 99%
“…However, Vestergaard et al [ 12 ] found that the Danish TeleCare North HF trial led to cost savings and was cost-effective in terms of health-related quality of life in favour of the intervention. Isaran et al [ 13 ] studied remote patient monitoring in HF and chronic obstructive pulmonary disease (COPD), and found that the cost of emergency room visits and hospitalizations were reduced. For Germany, the CardioBBEAT trial investigated the cost-effectiveness of noninvasive telemonitoring as a primary endpoint.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study evaluating the use of an RPM solution in the care of exacerbation of COPD and chronic heart failure, Isaranuwatchai et al [ 8 ] studied the economic impact of remote monitoring symptoms to detect early deterioration of patient health. It is, therefore, somewhat suited to an evaluation in the context of monitoring of acute conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This study showed a potential reduction of 68% and 35% in the number of emergency room (ER) visits and hospitalizations, respectively, between the 3-month pre– and post–RPM intervention periods. The average ER visit cost was reduced from CA $243 (~US $191) at the baseline to CA $67 (~US $53) during the 3-month follow-up and from CA $3842 (~US $3023) to CA $1399 (~US $1100) for hospitalization [ 8 ]. This result demonstrates that an RPM solution can not only free-up resources but also lead to a less resource-heavy and, therefore, less-expensive visit or admission in the context of acute care.…”
Section: Introductionmentioning
confidence: 99%
“…In the pre-COVID-19 period, clinical adoption was primarily driven by financially incentivizing models. Traditional telemedicine, for example, potentially reduced the use of high-cost in-person resources, and hospital admissions and readmissions for populations with heart failure and chronic obstructive pulmonary disease 12 – 15 . Such savings were relevant with capitated payer models, while real-world savings in fee-for-service settings have been less clear and are being investigated 16 .…”
Section: Epoch I: Digital Health In Academic Health Institutions Befo...mentioning
confidence: 99%